2003
DOI: 10.3141/1848-03
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Framework for Strategic Assessment of Transportation Policies: Application for Athens 2004 Olympic Games

Abstract: Consistent decision making requires a structured, systematic evaluation of the advantages and disadvantages of different choice possibilities. For the evaluation of transportation policy measures, various multicriteria analysis (MCA) methods have been developed to complement conventional cost–benefit analysis. These methods investigate and evaluate all relevant effects of an alternative by introducing some key policy criteria that are particularly relevant in assessing strategic-level impacts, such as environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…For example, CBA was employed in the Trans-Pennine Corridor (TPC) SEA in Northern England in 1997 (Dalkmann, 2001), also in Maastricht Aachen Airport (MAA) expansion SEA in southern Netherlands (Vreeker et al, 2002). In a SEA for the transportation policy of the 2004 Athens Olympic Games, both CBA and MCA were adopted as the central tools (Tsamboulas and Kopsacheili, 2003). A variety of possible techniques used for conducting the different steps of SEA were further analyzed and discussed in the literature including DHV (1994), Partida ´rio (2002), Sadler (1996), The ´rivel (2004) and UNEP (2002).…”
Section: Techniques and Methodologies Of Seamentioning
confidence: 99%
“…For example, CBA was employed in the Trans-Pennine Corridor (TPC) SEA in Northern England in 1997 (Dalkmann, 2001), also in Maastricht Aachen Airport (MAA) expansion SEA in southern Netherlands (Vreeker et al, 2002). In a SEA for the transportation policy of the 2004 Athens Olympic Games, both CBA and MCA were adopted as the central tools (Tsamboulas and Kopsacheili, 2003). A variety of possible techniques used for conducting the different steps of SEA were further analyzed and discussed in the literature including DHV (1994), Partida ´rio (2002), Sadler (1996), The ´rivel (2004) and UNEP (2002).…”
Section: Techniques and Methodologies Of Seamentioning
confidence: 99%
“…Among the initiatives corresponding to the highest importance factors are Economic Accessibility in the UPT (9.4%), Universal Accessibility to the UPT (9%), and Promotion of public safety (8.6%), which corroborates the study of Sdoukopoulos [47], where mobility, accessibility, and safety are identified as the most significant topics included in a wide range of initiatives. From an economic point of view, accessibility is considered an important competitiveness factor that can explain a higher economic growth [52]. Likewise, the introduction of accessibility metrics in public transport planning allows the development of new evidence and arguments for the redistribution of means of transport that can reduce the environmental and spatial pressure of urban road transport [53,54].…”
Section: Results Of the Experts' Judgmentsmentioning
confidence: 99%
“…For the staging of global sport events, transportation comprises three core aspects: First, it is about the transportation of goods to fulfil event or venue requirements (Herold et al, 2020); second, the transportation of athletes or teams including their associated support staff; and third, the management of (public) transportation of fans and spectators to the event location and venues (Kassens-Noor, 2019;Tsamboulas & Kopsacheili, 2003). The first aspect comprises classical logistics tasks; for instance, for the 2012 London Olympic Games, UPS transported 10,500 beds sourced in China and Malaysia through their transportation network (Wilding, 2012).…”
Section: Transportationmentioning
confidence: 99%